Building statistical analysis maps using geographic information systems for primary schools in Al-Zubair City - Ammar A. Hussain Mendlawy ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Those who follow the course of development in cartography clearly notice the rapid escalation of applied work in many fields of geographical research in general, cartography in particular, and statistical applications accurately, and this study is one of them, as it confirms that statistical maps are a type of objective maps that can be used to solve a number of Problems and complications in our daily life . As statistical analyzes were adopted to reveal the pattern of geographical distribution of primary schools in the city of Al-Zubayr in the province of Basra in Iraq, the density of these schools, the pattern of their spread, and the scope of service they perform for the population in the city’s neighborhoods and their output in the form of objective maps, through which it was found that the distribution of these schools was defective. It is clear that this calls for a review of future plans for the expansion of the city and real solutions to current and future problems in this area.